Research Progress on Drug-loaded Nanofibers Prepared by Electrospinning - MA Yue-long; LI Jia; WANG Hong (Journal of Harbin University of Science and Technology)
The nanofibers prepared by electrospinning have a porous structure and a large specific surface area. They are widely used in protective clothing, filter membrane, wound dressing and other fields. With the advancement in the medical field, the nanofibers prepared by electrospinning have become increasingly prominent as drug carriers. The drugs in the nanofibers can be released effectively and continuously by different drug-loaded methods. Therefore, the nanofiber is considered as one of the ideal materials in the field of drug release and tissue engineering. In this paper, the principle of electrospinning and the research progress of electrospinning in the field of cont:J.·olled山ug release are mainly discussed. It provides a theoretical basis for the modification and application of controlled drug release fibers in future.